2016
DOI: 10.1002/lary.26186
|View full text |Cite
|
Sign up to set email alerts
|

Blunt cerebrovascular injury following craniomaxillofacial fractures: A systematic review

Abstract: N/A. Laryngoscope, 127:79-86, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 44 publications
(661 reference statements)
2
3
0
Order By: Relevance
“…The mean age of the participants with CMF fractures in our study was 23.94 ± 17.40 years, which is similar to the average of 25.75 ± 15.5 years found in another study [17]. Upper facial fractures were the least prevalent type of CMF fractures, a finding corroborated by two other studies to date [18,19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mean age of the participants with CMF fractures in our study was 23.94 ± 17.40 years, which is similar to the average of 25.75 ± 15.5 years found in another study [17]. Upper facial fractures were the least prevalent type of CMF fractures, a finding corroborated by two other studies to date [18,19].…”
Section: Discussionsupporting
confidence: 90%
“…However, several studies support our findings [2,25,26], while some others do not. A systematic review identified 410 BCVI cases among 90,968 blunt trauma admissions with CMF fractures, constituting an overall incidence of 0.45% [18]. The mean age of BCVI patients in our study was 46.91 ± 17.04 years, similar to that in Weber et al's study (46 ± 19 years) [25].…”
Section: Discussionsupporting
confidence: 83%
“…As Le Fort fractures often present in patients who have sustained polytrauma, risk factor analysis of this patient population has typically focused on identification of predictors of associated injuries. Indeed, studies have shown that Le Fort fractures confer a significantly increased likelihood of sustaining sight-threatening ocular trauma, 29,30 blunt cerebrovascular injury, 31,32 and cervical spine injury. 33 It is therefore not surprising that a recent, single institution retrospective study by Lucke-Wolde et al 34 proposed an algorithm for management of patients with traumatic brain injury and facial fractures and found that patients with Le Fort II and III fractures were more likely to require neurosurgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Many diagnostic modalities exist for the diagnosis of DA including ultrasonography, CT, magnetic resonance imaging, and conventional angiography, which is the gold standard in diagnosing arterial dissections. 12 Angiography of a DA classically demonstrates irregular narrowing of the vessel lumen or aneurysmal dilatation. 14 In this case, the conventional angiography revealed narrowing of the extracranial part of the ICA, thus confirming the diagnosis of DA.…”
Section: Discussionmentioning
confidence: 99%